Personal and Social Transformation in the Health Area through Education: A Brief Journey from the Ancestral Indigenous Wisdom to the Modern Tyranny of Healthiness - Andrés de Muller (Universidad Nacional, Costa Rica, 2015)
This paper aims at claiming the ancestral wisdom of indigenous people in the health area. It analyzes how health has been commodified in the interest of large companies (particularly those related to the pharmaceutical industry) to the detriment of a holistic definition of wellness through education. Furthermore, the concept of health as a right disagrees with such commodification or sale to the highest bidder, which prompts dehumanization of health services and public misinformation. The abundance of self-proclaimed gurus or healers who appeal to autosuggestion contributes both to confusion and to an unhealthy cult of healthiness.